The quality of problem-oriented teaching and student achievement - Nataša T. Nikolić (University of Belgrade, Teacher Education Faculty, 2019)
The paper analyses the possibilities and ways of implementing problem-oriented teaching in the classroom. The goal of the research was to expand the existing knowledge about the level of representation, quality of implementation, and the characteristics of the problem-oriented teaching, as well as about the effect of this form of teaching on the level and quality of student achievement in biology and mathematics. The research involved 97 mathematics teachers, 99 biology teachers, and a total of 1117 students. A descriptive-analytical method was used and the data was collected by using scaling, surveying, and testing techniques. The research results indicate that problem-oriented teaching is the most frequently used teaching approach in the mathematics classroom, while it is used to a lesser extent in teaching biology. The students whose teachers frequently use problem-oriented teaching achieve better results than students who are rarely exposed to this type of teaching and learning. As far as the type of problem is concerned, students mostly have to solve problems containing more information in the text, while the problems with several correct solutions are rarely used. Students generally realize that problem-solving the process involves the activities pertaining to the problem-oriented teaching and learning. The analysis of the quality of implementation showed that students do not pay enough attention to initial activities in the problem-solving process and to the evaluation of the achieved results. Positive correlations were established between the analyzed characteristics of the problems and student achievement, as well as between the frequency and quality of problem-oriented teaching activities and student achievement. Problem-oriented teaching is mostly implemented at revision classes by using a dialogue method and individual interaction pattern in teaching mathematics, while frontal interaction pattern is mostly used in biology classes.